Wearable inertial sensors for clinical gait analysis in Parkinson’s disease: a test-retest reliability study - Angkurasiripaiboon, Thanakorn; Stonsaovapak, Chernkhuan; Justine, Maria; Siriphorn, Akkradate (Journal of Associated Medical Sciences, 2025)
Background: Parkinson’s disease (PD) is a neurodegenerative disorder that significantly affects gait parameters. Accurate and reliable gait assessment tools are essential for monitoring disease progression and treatment efficacy. The G-Walk®,a wearable inertial measurement device, offers a convenient and portable solution for evaluating spatiotemporal gait parameters, but its reliability in individuals with moderate-stage PD remains underexplored. Objectives: This study aimed to evaluate the test-retest reliability of the G-Walk® sensor system in assessing gait parameters in individuals with moderate-stage PD. Materials and methods: Thirteen participants with idiopathic PD completed two walking trials on a 14-meter pathway, conducted 3 to 7 days apart. Gait parameters, including stride length, cadence, gait velocity, and limb support times, were recorded using the G-Walk® system. Intraclass correlation coefficients (ICCs), standard error of measurement (SEM), and minimal detectable change (MDC) were calculated. Results: The G-Walk® system demonstrated excellent reliability for stride length (ICC=0.979), cadence (ICC=0.958), and gait velocity (ICC=0.997). Moderate reliability was observed for single limb support (ICC=0.699) and double limb support times (ICC=0.656). SEM and MDC values further supported the precision of the system for clinical applications. Conclusion: The G-Walk® sensor system is a reliable tool for assessing gait parameters in individuals with moderate-stage PD, particularly for stride length, cadence, and gait velocity. Its portability and ease of use make it suitable for clinical settings to track disease progression and evaluate interventions.